Treatments to optimize the use of artificial insemination and reproductive efficiency in beef cattle under tropical environments - De Sá Filho, Ocilon Gomes [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Hindawi, 2011)
Bos indicus cattle, the preferred genetic group in tropical climates, are characterized by having a lower reproductive efficiency than Bos taurus. The reasons for the poorer reproductive efficiency of the Bos indicus cows include longer lengths of gestation and postpartum anestrus, a short length of estrous behavior with a high incidence of estrus occurring during the dark hours, and puberty at older age and at a higher percentage of body weight relative to mature body weight. Moreover, geography, environment, economics, and social traditions are factors contributing for a lower use of reproductive biotechnologies in tropical environments. Hormonal protocols have been developed to resolve some of the reproductive challenges of the Bos indicus cattle and allow artificial insemination, which is the main strategy to hasten genetic improvement in commercial beef ranches. Most of these treatments use exogenous sources of progesterone associated with strategies to improve the final maturation of the dominant follicle, such as temporary weaning and exogenous gonadotropins. These treatments have caused large impacts on reproductive performance of beef cattle reared under tropical areas. Copyright © 2011 O. G. Sá Filho and J. L. M. Vasconcelos.
Keywords: Bos; Bos indicus; Bos taurus